2018
DOI: 10.5171/2018.79814
|View full text |Cite
|
Sign up to set email alerts
|

Drawbacks and Limitations of Black-Scholes Model for Options Pricing

Abstract: The present paper focuses on the methods of derivative contract pricing. The basic differential equation of the popular Black-Scholes model for option contract pricing is derived. Furthermore, its less known modifications by Merton and Garman and Kohlhagen are pointed out. The paper refers to the significant drawbacks and limitations of the option pricing models that are based on constricting and unrealistic assumptions that often fail in comparison to the real market data. Attention is paid to the most seriou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…For instance, it assumes that during the lifetime of the option no dividend is paid, that risk-free rate and volatility are constant, and the movement of the market cannot be predicted but in the real world, usually, this cannot happen. Likewise, Janko has studied the drawbacks and limitations of the Black-Scholes model and concluded that "another strong prerequisite necessary for the derivation of the Black-Scholes model is the perfect derivative replication by the share and a risk-free instrument; however, this cannot be achieved without transaction costs" [12][13]. This means B-S formula does not consider the transaction cost.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it assumes that during the lifetime of the option no dividend is paid, that risk-free rate and volatility are constant, and the movement of the market cannot be predicted but in the real world, usually, this cannot happen. Likewise, Janko has studied the drawbacks and limitations of the Black-Scholes model and concluded that "another strong prerequisite necessary for the derivation of the Black-Scholes model is the perfect derivative replication by the share and a risk-free instrument; however, this cannot be achieved without transaction costs" [12][13]. This means B-S formula does not consider the transaction cost.…”
Section: Discussionmentioning
confidence: 99%
“…For Al-Zhour et al [2] investigated pricing using a nonlinear volatility model. Jankova [6] focused on the methods of derivative contract pricing, and derived the basic differential equation of the Black-Scholes model for option contract pricing. He also referred to the significant drawbacks and limitations of other option pricing models which are based on unrealistic assumptions.…”
Section: Preliminariesmentioning
confidence: 99%
“…Nowadays many different option contracts are traded. They are divided into call and put contracts giving the owner the right to buy or sell an asset (Hull et al, 1987;Jankova, 2018), respectively. The option contract may be signed for a few days as well as for a several months.…”
Section: Introductionmentioning
confidence: 99%
“…This approach includes also linear Black-Scholes option pricing model (Ivancevic, 2011;Wróblewski, 2017) having the form of the linear parabolic boundary value problem with constant coefficients. The option trading practice indicates, that the assumptions of linear Black-Scholes option pricing model are simplification (Hull et al, 1987;Jankova, 2018) of the real market conditions. Assuming in this linear model stochastic volatility or interest rate we can extend and transform it into non-linear model.…”
Section: Introductionmentioning
confidence: 99%